2009
DOI: 10.3390/e11040634
|View full text |Cite
|
Sign up to set email alerts
|

A Lower-Bound for the Maximin Redundancy in Pattern Coding

Abstract: We show that the maximin average redundancy in pattern coding is eventually larger than 1.84for messages of length n. This improves recent results on pattern redundancy, although it does not fill the gap between known lower-and upper-bounds. The pattern of a string is obtained by replacing each symbol by the index of its first occurrence. The problem of pattern coding is of interest because strongly universal codes have been proved to exist for patterns while universal message coding is impossible for memoryle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This remarkably simple method is however expected to have a poor performance when α is large. Indeed, it is proved in Garivier (2006) that R + Ψ (Ψ 1:n ) is lower-bounded by 1.84 n log n 1 3 (see also Shamir (2006) and references therein), which indicates that pattern coding is probably suboptimal as soon as α is larger than 3.…”
Section: A Pattern Codingmentioning
confidence: 99%
“…This remarkably simple method is however expected to have a poor performance when α is large. Indeed, it is proved in Garivier (2006) that R + Ψ (Ψ 1:n ) is lower-bounded by 1.84 n log n 1 3 (see also Shamir (2006) and references therein), which indicates that pattern coding is probably suboptimal as soon as α is larger than 3.…”
Section: A Pattern Codingmentioning
confidence: 99%
“…For example, the pattern of "banana" is 123232 and its dictionary is 1 → b, 2 → a, and 3 → n. Letting ∆ n ψ denote the collection of all pattern distributions, induced on sequences of length n by all i.i.d. distributions over any alphabet, a sequence of papers , Shamir [2006Shamir [ , 2004, Garivier [2009], , Acharya et al [2012Acharya et al [ , 2013 showed that although patterns carry essentially all the entropy, they can be compressed with redundancy 0.3 · n 1/3 ≤R(∆ n ψ ) ≤R(∆ n ψ ) ≤ n 1/3 · log 4 n as n → ∞. Namely, pattern redundancy too is sublinear in the block length and most significantly, is uniformly upper bounded regardless of the alphabet size (which can be even infinite).…”
Section: Previous Resultsmentioning
confidence: 99%
“…For example, the pattern of "banana" is 123232 and its dictionary is 1 → b, 2 → a, and 3 → n. Letting ∆ n ψ denote the collection of all pattern distributions, induced on sequences of length n by all i.i.d. distributions over any alphabet, a sequence of papers , Shamir [2006Shamir [ , 2004, Garivier [2009], , Acharya et al [2012Acharya et al [ , 2013 showed that although patterns carry essentially all the entropy, they can be compressed with redundancy…”
Section: Previous Resultsmentioning
confidence: 99%
“…Unlike the mostly finite-alphabet results referred to so far, this paper is concerned with adaptive coding over a countably infinite alphabet X (say the set of positive integers N + or the set of integers N) as described for example in Kieffer (1978); Gyorfi et al (1993); Foster et al (2002); Orlitsky and Santhanam (2004); Ryabko et al (2008); Boucheron et al (2009); Garivier (2009); Bontemps (2011); Gassiat (2014); Bontemps et al (2014). This does not preclude the finite-alphabet case, which becomes a special instance.…”
Section: Contributions and Organization Of The Papermentioning
confidence: 99%